Amalan syura dalam kepimpinan guru besar dan hubungannya terhadap komitmen kerja guru - Abd. Hamid, Suhana (2017)
The practice of Shura by headmasters through discussion and by making decision together with the teachers is believed to give great impacts to teachers’ work commitment. Thus, failing to do so will reduce teachers’ work commitment. For the matter, the study has constructed a Shura framework based on the leadership of the Prophet Muhammad. The objective of this research is to examine the implementation of Shura practice among headmasters in Islamic schools in Johor Bahru district and its relation with teachers' work commitment. Leadership elements that have been studied include openness, consensus, trust, advice, and amanah. While the elements of teachers’ commitment encompass responsibility, cooperation, discipline, competence, and organisational relationship. Besides that, this study also studied whether there is a significant relationship between the elements of Shura under the headmasters’ leadership with teachers' work commitment. This study used quantitative design with the questionnaire as a fundamental data acquisition. A total of 200 teachers from 23 Grade A Islamic schools in Johor Bahru were selected as respondents of this study. The data was analysed using the Statistical Package for The Social Science (SPSS) 22.0. The results showed that the practice of Shura under the headmasters’ leadership was high with a Cronbach’s alpha value of 0.946. The study found that the five elements of the Shura practice have a significant relationship towards the increase of teachers' work commitment. The element of openness is the key element in Shura leadership which proved that the headmasters should always apply openness to achieve a dynamic increase in work commitment. Shura framework was built based on the leadership of Prophet Muhammad as a guideline towards a holistic leadership and it encourages the increase in sustainable teachers' work commitment. In conclusion, the implication of Shura leadership helps to ensure an outstanding educational performance in school and produce competent students.